Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1007/s11120-010-9598-9
|View full text |Cite
|
Sign up to set email alerts
|

Singlet and triplet excited state properties of natural chlorophylls and bacteriochlorophylls

Abstract: Ten naturally occurring chlorophylls (a, b, c (2), d) and bacteriochlorophylls (a, b, c, d, e, g) were purified and studied using the optical spectroscopic techniques of both steady state and time-resolved absorption and fluorescence. The studies were carried out at room temperature in nucleophilic solvents in which the central Mg is hexacoordinated. The comprehensive studies of singlet excited state lifetimes show a clear dependency on the structural features of the macrocycle and terminal substituents. The w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
116
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(128 citation statements)
references
References 37 publications
(30 reference statements)
10
116
2
Order By: Relevance
“…These values are larger than those calculated from the spectral densities with the standard prefactor [65] in our previous paper [22]. Our MD/TDDFT calculations imply that the reorganization energies of the BChl d in the roll is larger than that in solvent (69 cm −1 ) [66]. This large reorganization energy can be a signature of a fast energy relaxation within Q y exciton states in the roll.…”
Section: A Spectral Densitiescontrasting
confidence: 58%
“…These values are larger than those calculated from the spectral densities with the standard prefactor [65] in our previous paper [22]. Our MD/TDDFT calculations imply that the reorganization energies of the BChl d in the roll is larger than that in solvent (69 cm −1 ) [66]. This large reorganization energy can be a signature of a fast energy relaxation within Q y exciton states in the roll.…”
Section: A Spectral Densitiescontrasting
confidence: 58%
“…TRF measurements were carried out using the laser system and universal streak camera setup described in detail previously (52), exciting at 602 nm. The spectra were cleared from noise and globally fit using the program ASUfit (13).…”
Section: Methodsmentioning
confidence: 99%
“…In oxidizing conditions, the fast lifetime of the quenching pathway (60 ps) is thought to compete with the rate of energy transfer to the RC. This pathway effectively disappears in reducing conditions, allowing the pigments to fluoresce with lifetimes similar to that of monomeric BChl a (2 ns) (13). It was suggested that the quenching effect might be controlled by a modified aromatic amino acid (e.g., tyrosylquinone or trytophylquinone) that plays a role similar to that of the excitation-quenching quinones found in the chlorosome (12).…”
mentioning
confidence: 99%
“…As light harvesters, carotenoids transfer the absorbed excited state energy to (bacterio)chlorophylls ((B)Chl); this excitation energy is eventually trapped by a reaction centre pigment -protein complex and converted into an electrical potential [19,20]. They also act as protective molecules against the photobleaching of photosynthetic organisms by quenching (B)Chl triplet states [21,22], which prevents the (B)Chlsensitized formation of singlet state oxygen [23][24][25][26][27][28][29], by scavenging singlet oxygen directly [8,30] or by quenching (B)Chl singlet states [31 -33]. Carotenoids have also been reported to stabilize protein structures, because many photosynthetic pigment -protein complexes do not fold properly without these molecules [34 -36].…”
Section: Introductionmentioning
confidence: 99%